Psychometric Characteristics of The Persian Version of The Self-Efficacy to Regulate Exercise Questionnaire Among Female Adolescents - Masoumeh Motamedi; Nooshin Peyman; Jjamshid Jamali; Monavar Afzalaghaee (Mashhad University of Medical Sciences, 2020)
Background and Objective: The positive effects of regular physical activity are already approved in all age groups. However, sedentary life style among teenagers is common all around the world. The understanding of self-efficacy can help to maintain and improve health promoting behaviors. This study aimed at psychometric evaluation of the Persian version of the Self-Efficacy to Regulate Exercise Questionnaire (SEREQ) among 15 to 18-year-old girls.Materials and Methods: In order to evaluate psychometric characteristics of the Persian version of the SEREQ, 439 students were randomly selected by the cluster sampling method from different educational districts. After translating the questionnaire using the Joan's approach, its validity and reliability were evaluated by the Cronbach's alpha, content validity indicators, content validity index and Confirmatory factor analysis.Results: The students' mean age was 16.51±1.04 years and their mean BMI was 21.40±3.64. The content validity indicators (0.98) and content validity index (0.97) were at an acceptable level for all the questionnaire's items. The level of Cronbach's alpha among the SEREQ questions was 0.898. Confirmatory factor analysis findings showed acceptable fit indices (CFI = 0.946, TLI = 0.934, RMSEA = 0.049, 2.067 = 125/258   =d/2).Conclusion: The findings of the current study showed that the SEREQ has acceptable validity and reliability in Persian version and can be used to evaluate the efficacy of regular physical activity among Iranian female adolescents.